Molecular characterization of bovine rotavirus circulating in beef and dairy herds in Argentina during a 10-year period (1994–2003) - Garaicoechea, Lorena Laura (2006)
Group A bovine rotavirus (BRV) is one of the main causes of neonatal calf diarrhea. The present study reports the incidence of rotavirus diarrhea and the genotypes of BRV strains circulating in beef and dairy herds from Argentina, during a 10-year period (1994-2003). Group A BRV was detected in 62.5% (250/400) of the total studied cases of diarrhea. Positive cases were analyzed by heminested multiplex RT-PCR for P and G genotypes identification. Sixty percent of them were typed as P[5]G6, 4.4% P[11]G10, 4.4% P[11]G6 and 2.4% P[5]G10. Additionally, 9.2% of the cases were initially typed as G8 combined with P[5] or P[11], but sequence analysis revealed they belonged to genotype G6, lineage Hun4-like. Partial typing was assessed in 12.0% of the cases. One of the partially typed samples was closely related to genotype G15. BRV was detected in 71% and 58% of the outbreaks registered in beef and dairy farms, respectively. A clear differential distribution of G/P types was found according to the herd type. P[5]G6 was the prevalent strain in beef herds, while P[11] was the prevalent P-type in dairy herds (71%), associated in similar proportions with G6 and G10, These findings indicate that BRV genotypes included in the current commercially available rotavirus vaccines (G6, G10, P[5] and P[11]) should protect calves from most Argentinean field strains. Nevertheless, continuous surveillance is necessary to detect the emergence of new variants.